Left Subclavian Artery Pseudoaneurysm after a Traffic Accident: A Case Report - J. Enamorado-Enamorado; J. J. Egea-Guerrero; J. Revuelto-Rey; E. Gordillo-Escobar; C. Herrera-Melero (Case Reports in Critical Care)
The left subclavian artery pseudoaneurysm is a rare entity with few cases reported in the literature. Most injuries were related to iatrogenic manipulation with catheters for canalization of central lines. In rare cases, this injury has been described secondary to a blunt trauma. We present an unusual case of pseudoaneurysm that includes the origin of left subclavian artery in the context of severe multiple injuries after a traffic accident. There were not clavicular or rib fractures, or another type of chest trauma to justify such a vascular injury. Once the injuries that were life threatening for the patient were stabilized, it proceeded to the treatment of the pseudoaneurysm by placing an endovascular prosthesis successfully with a favorable clinical evolution.